2017
DOI: 10.1016/j.ijthermalsci.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rectangular winglet pair roll angle on the heat transfer enhancement in laminar channel flow

Abstract: Convective heat transfer enhancement can be achieved by generating secondary flow structures that are added to the main flow to intensify the fluid exchange between hot and cold regions in the system. One method involves the use of vortex generators to produce streamwise and transverse vortices on the top of the main flow. This study presents numerical computation results on laminar convection heat transfer in a rectangular channel which bottom wall is equipped with rectangular winglet pair vortex generators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…According to their results, a small fin and a large open angle cause a strong flow deflection, resulting in a large share of windows. A numerical investigation on the influence of using rectangular winglet pairs on the thermal performance of a rectangular channel is done by Khanjian et al [111]. Based on the results, it is indicated that the heat transfer improved by increasing the roll angle of vortex generators.…”
Section: Wingletsmentioning
confidence: 99%
“…According to their results, a small fin and a large open angle cause a strong flow deflection, resulting in a large share of windows. A numerical investigation on the influence of using rectangular winglet pairs on the thermal performance of a rectangular channel is done by Khanjian et al [111]. Based on the results, it is indicated that the heat transfer improved by increasing the roll angle of vortex generators.…”
Section: Wingletsmentioning
confidence: 99%
“…Nonetheless, the secondary flows triggered by longitudinal vortices will disrupt the formation of thermal boundary layers and cause flow instability, which in turn produces turbulence with high scale [7]. In addition, the vortices generated by longitudinal VG (LVG) last a long time until reaching the downstream region [8].…”
Section: Introductionmentioning
confidence: 99%
“…Vorticity is an inherent feature of fluid flow and is often considered as an efficient mechanism in the heat and mass transfer phenomena. In many situations of practical interests vorticity is artificially generated to enhance heat and mass transfer [1][2][3][4][5][6][7][8][9][10], but also vorticity exists naturally in many types of fluid flows such as in the near-wall region of turbulent boundary layers [11,12] or surfaces with curvature and/or rotation [13][14][15]. Physical understanding of the mechanism of heat transfer by vorticity is therefore crucial for active and passive control in numerous technological applications [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%